MORPHOLOGICAL CHARACTERS AND GENETIC VARIABILITY OF CHAMPACA IN BALI - I Made Sukewijaya; Made Sudiana Mahendra; I Nyoman Rai; I Gede Rai Maya Temaja (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2016)
Bali community utilize champaca flower for offering materials and worship, besides beauty salon purposes, the SPA aromatic ingredients, essential oils, perfumes, cosmetics, and drugs. Various champaca plants in Indonesia have not been studied as one of Indonesia's biodiversity that can be used as excellent genetic resources (germplasm). The objective of the study was to determine the genetic diversity of champaca in Bali. The results revealed that 12 (twelve) champaca accession morphologically was characterized. All of accessions obtained from cultivation centers champaca in Bali. Based on the characteristic was observed by morphological characters i.e.: (a) Cempaka Putih Wilis (b) Cempaka Putih Pateh, (c) Cempaka Putih Patemon, (d) Cempaka Putih Sibang, (e) Cempaka Kuning Muda Petemon, (f) Cempaka Kuning Kecil Patemon, (g) Cempaka Kuning Besar Patemon, (h) (i) Cempaka Kuning Kecil Sibang, (j) Cempaka Kuning Tua Sibang, (k) Cempaka Kuning Muda Sibang, and (l) Cempaka Kuning Punah Sibang. Morphologically, champaca in Bali can be grouped into 4 clusters and therefore, and based on RAPD analysis champaca in Bali could be grouped into 5 clusters.